2021
DOI: 10.3390/su14010002
|View full text |Cite
|
Sign up to set email alerts
|

Hegemony of Network Capabilities, Frugal Innovation and Innovation Strategies: The Innovation Performance Perspective

Abstract: The emergence of advanced technologies has brought new challenges and opportunities for all kinds of business organizations. In a technologically advanced era, innovation plays a dominant role for the successful operation of the commercial landscape. Therefore, the current study was conducted to investigate the impact of network capabilities (NC) and frugal innovation (FI) on innovation performance (IP). Furthermore, the mediating role of FI and moderating role of innovation strategies has also been tested on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
2
3
0
2
Order By: Relevance
“…This study also demonstrated the significant and positive influence of innovation orientation on both competitive advantage (H5a) ( t = 5.110, p = 0.000) and economic sustainability (H5b) ( t = 4.904, p = 0.000). This present study supported the study of Haffar et al ( 2022 ), which pointed out that organisations in any level should have enough information and network to expand and create strategic position in a highly competitive market. Thus, both H5a and H5b were accepted.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This study also demonstrated the significant and positive influence of innovation orientation on both competitive advantage (H5a) ( t = 5.110, p = 0.000) and economic sustainability (H5b) ( t = 4.904, p = 0.000). This present study supported the study of Haffar et al ( 2022 ), which pointed out that organisations in any level should have enough information and network to expand and create strategic position in a highly competitive market. Thus, both H5a and H5b were accepted.…”
Section: Resultssupporting
confidence: 91%
“…Network orientation can be successfully implemented to achieve a strategy when an organisation is able to combine networking capability and human networking. This finding was found to be in line with the finding of Haffar et al ( 2022 ) on the necessity of network orientation for knowledge transfer, helping SMEs to innovate and move towards what strategies needed to implement in a hyper-market competition. The study also found that organisations require information about market conditions and customers’ needs, suggesting the importance of network orientation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Dukungan inovasi mempunyai efek moderat, sehingga dampaknya berpengaruh terhadap kinerja keuangan (Fahad et al, 2021). Perkembangan bisnis yang mengalami perubahan, dan demi kelangsungan bisnis UKM, maka UKM perlu untuk melakukan inovasi pada produk dan layanan (Haffar et al, 2022).…”
Section: Otonomiunclassified
“…Hal tersebut berarti bahwa inovasi yang telah diimplementasikan pada bisnis UMKM akan berdampak pada peningkatan kinerja bisnis. Penelitian pada pebisnis UMKM di Kabupaten Kudus Ini sejalan dengan penelitian sebelumnya yang dilakukan oleh (Jamai et al, 2021); (Fahad et al, 2021); dan (Haffar et al, 2022).…”
Section: Pengaruh Inovasi Terhadap Kinerja Bisnis Umkmunclassified